Antioxidant Property of Jobelyn as the Possible Mechanism Underlying its Anti-amnesic Activity in Rodents - Solomon Umukoro; Adaeze Ugbomah; Adegbuyi O. Aderibigbe; Anothony T. Eduviere; Adrian I. Omogbiya (Basic and Clinical Neuroscience, 2013)
Introduction: Amnesia or loss of memory is the cardinal hallmark of Alzheimer’s disease (AD), a progressive neurodegenerative disorder associated with ageing process. Although, AD had been discovered over a century ago, drugs which could cure or halt the progression of the disease are yet to see the light of the day. However, there has been a growing interest in the use of phytomedicines with multipronged mechanisms of action that could target various aspects of the pathologies of AD. Jobelyn (JB) is a potent antioxidant African polyherbal formulation with active components that have been acclaimed to show neuroprotection. This investigation was carried out to evaluate whether JB has anti-amnesic and antioxidant activities.